Pengaruh Video Animasi Terhadap Minat Belajar Peserta Didik Pada Mata Pelajaran Matematika - Anna Nurjanah; Riza Fatimah Zahrah; Geri Syahril Sidik (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
According to Law No. 20 of 2003 concerning the National Education System, education is a conscious and planned effort to create a learning atmosphere and learning process so that students actively develop their potential to have the spiritual power of religious rituals, self-control, personality, intelligence, noble morals, and the necessary skills. by himself, society, nation, and state. Learning media is a tool in the teaching and learning process that conveys messages and clarifies material to help the learning process. Observations carried out at SDN Sukamulya still used media such as pictures on paper or were only guided by the textbooks used. From these results, students had no interest in the learning process if they only used paper media. The aim of this research is to determine the effect of learning videos on interest in learning mathematics for class V at SDN Sukamulya. The research method used was an experiment with a quantitative approach design to determine how variable the results were. From the pretest results, it was 23.64%, and the posttest results increased to 25.76%.